Effects of obesity in labour market outcomes: evidence from Malaysia - Foo, Lee Peng; Hamzah, Hanny Zurina; Mohamed Nor, Norashidah; Said, Rusmawati (Universiti Putra Malaysia Press, 2018)
With the aims to shed light on the relationship between obesity and labour market outcomes in Malaysia, the ordinal regression model was applied on the collected questionnaires. The result from the three models suggests that employers do not consider workers' appearance and gender when they employ workers. After all, they are more concern about performance, education background and age when recruiting their ideal staff member. Even though this study fails to prove the existence of discrimination which has led to lower wages among Malaysians, the result of this study has proven that obese workers receive unfavorable treatment. Since the prevalence of obesity among Malaysian adults is substantial, the outcome of this study is crucial as it gives comprehensive information on the impact of obesity on the labour market outcome in Malaysia. The information from this study may help the authorities how to develop activities and programs in fighting obesity and how to encourage Malaysian to maintain healthy lifestyle.